Rehabilitasi Psikososial berbasis Rumah Sakit sebagai Upaya Sustainable bagi ODGJ di Kabupaten Gresik - Khamida; Hafid Algristian; Difran Nobel Bistara; Fifi Khoirul Fitriyah; Abdul Hakim Fasya (Warmadewa University Press, 2023)
Treatment for people with mental disorders (orang dengan gangguan jiwa, ODGJ) in Gresik Regency is still limited to curative (medication) because Gresik Regency does not yet have adequate psychosocial rehabilitation facilities (RPS). RPS aims to restore the social functions of ODGJ so that they are more productive according to their abilities. Activity goals. To initiate the hospital-based RPS activities. Problem-solving framework. The framework is carried out through several activities, such as conducting assessments and focused group discussions with hospitals managers as potential partners, creating RPS service guidelines, conducting training and upgrading skills for health workers, involving ODGJ, families, and health cadres in RPS services, and planning a follow-up with the community health center (community health center, puskesmas), social institutions, and local officials. Results. Grha Husada Gresik Hospital (RSGH) is willing to initiate RPS services in Gresik Regency. This RPS service will be carried out for a minimum of two years, with ODGJ clinical evaluations every three months. The RSGH’s advantage is that it has 4 (four) certified health workers as behavior therapists for children with special needs (ABK). The RPS module was made by modifying the ABK behavior therapy module to suit the needs of adult ODGJ. RPS training is carried out based on the module. A total of 30 participants attended the initial RPS service, consisting of 10 ODGJ patients, 10 companions, and 10 local health cadres. The consistency of the arrival of ODGJ and companions is still low, due to the lack of awareness of the benefits of RPS services. RSGH and the health cadres took the initiative together to pick them up, but the arrival rate was still around 5-6 people per meeting. Conclusion. Good cooperation between hospitals, health cadres, and families is the first step for sustainable RPS services. The main challenge is to raise awareness of the need for RPS services for patients and their families.